Histology and Electrone Microscopic Study of the Efffects of an GnHR Agonist on the Canine 3 Months of Treatment - Aris Juniadi . (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2000)
Using light and electrone microscopic techniques the structure of the testicle, epididymis and prostate gland of mature male dogs were studied 3 months after implantation with a slow release irpplant containing 6 mg GnRH agonist. deslorelin. After 3 months of treatment, all tubules sipiniferous showed atropic and aspermatogenic. Atrophy of the Leydig cells was observed in the interstitial tissue. The glandular epithelium of the prostate showed atrophy and was non secretory. At the electrone microscopic levels, Sertoli and Leydig cells showed a marked atrophy and their spermatogenic tubules were mostly lined with Sertoli cells at the basal lamina. The prostate gland showed atrophy of the nucleous and the epithelium was non secretory_ The present data showed that a slow release implant containing GnRH agonist deslorelin can be used effectively to suppress fertility in male dogs.Key words: Testicle, epididymis, prostste gland, Leydig cell, Sertoli cell, GnRH agonist, deslorelin